Identification of clinical predictors for functional recovery in patients with thoracolumbar fractures and incomplete spinal cord injury: an internally validated prediction model - Li, Zongyang; Yao, Yudan; Qiao, Yu; Zhang, Li; Yu, Bin; Jiang, Yanpeng; Zhu, Yuhang (Frontiers in Neurology, 2026)
BackgroundAccurate prediction of functional recovery after thoracolumbar fracture with incomplete spinal cord injury (SCI) remains challenging. We aimed to identify independent predictors and develop a validated model for 12-month functional outcome.MethodsIn this single-center, retrospective cohort study (January 2018–December 2024), consecutive adults (≥18 years) with acute T11-L2 fractures and admission American Spinal Injury Association Impairment Scale (AIS) grade B, C, or D were enrolled. Functional recovery was defined as ≥1 AIS grade improvement plus ≥10-point Spinal Cord Independence Measure version III (SCIM-III) gain at 12 months. Candidate predictors (n = 23) were selected a priori based on literature review and expert consensus. Missing data (<8% per variable) were multiply imputed (m = 20). Multivariable logistic regression with Firth’s correction and backward elimination guided by Akaike Information Criterion was used. Model discrimination [optimism-corrected area under the curve (AUC) 0.87] and calibration (Hosmer-Lemeshow test) were assessed by 1,000 bootstrap resamples. Pre-specified subgroup analyses examined age, AIS grade, surgical timing and lesion length.ResultsAmong 1,032 eligible patients, 206 (20.0%) achieved functional recovery. Eight predictors were independently associated: admission AIS grade (OR 4.5 per grade, 95% CI 3.5–5.8), motor score (OR 1.05 per point, 1.03–1.07), intact posterior ligamentous complex (OR 2.3, 1.6–3.2), decompression ≤ 24 h (OR 1.9, 1.4–2.7), non-smoking (OR 1.7, 1.2–2.4), Charlson Comorbidity Index = 0 (OR 1.5, 1.1–2.1), shorter intramedullary T2 lesion length (OR 0.96 per mm, 0.95–0.97) and rehabilitation intensity ≥3 h/day (OR 1.4, 1.0–1.9). The final model demonstrated an optimism—corrected AUC of 0.87 (95% CI: 0.85–0.89) and calibration characteristics with a calibration slope of 1.02, an intercept of 0.01, and a Hosmer–Lemeshow p-value of 0.18 during internal validation. Predictive effects were stronger in younger, AIS B/C patients and when surgery was performed early.ConclusionA parsimonious eight-factor model showed robust discrimination and satisfactory calibration in internal validation for 12-month functional recovery after thoracolumbar incomplete SCI, enabling individualized prognostication. External validation in independent multicenter cohorts is required before clinical implementation and treatment decision-making.